Análise de estilos de orientação acadêmica na pós-graduação em Administração no Brasil - Dias, Cleysson Ricardo Jordão Braga (2024)
This thesis aims to analyze the academic mentoring styles identified in graduate programs in Administration in Brazil. The specific objectives were: (1) to characterize academic mentoring styles, (2) to develop a scale for academic mentoring styles, (3) to validate this scale, and (4) to verify the relationships between mentoring styles and the profiles of mentors in graduate programs in Administration in Brazil. The central argument of the research is that there are different academic mentoring styles in graduate programs in Administration, reflecting possible approaches adopted by mentors in the Brazilian context. To achieve the first objective, phenomenography was used, with interviews conducted with 23 productivity fellowship professors from various areas of Administration and at different career stages. For the second objective, a scale was developed to measure academic mentoring styles, which was administered to 527 graduate students in Administration. Exploratory Factor Analysis (EFA) was used to analyze the data. The scale validation, conducted for the third objective, was carried out using Confirmatory Factor Analysis (CFA) with a sample of 243 graduates of graduate programs in Administration. Finally, the fourth objective involved verifying the relationships between mentoring styles and mentor profile variables. A total of 236 professors responded to the survey, and descriptive statistics and the non-parametric Mann-Whitney U test were used for the analysis. The results of the phenomenographic study revealed four distinct mentoring styles: Pragmatic, Coach, Learner, and Affectionate. The results of the academic mentoring styles scale identified two predominant styles: Relational-Empathetic and Technical-Instrumental. The scale validation demonstrated its consistency in measuring these styles. Additionally, significant differences were found between mentoring styles and gender, with a possible predominance of the Relational-Empathetic style among women. A significant difference was also observed between the mentoring styles and professional graduate programs, suggesting a higher presence of both styles in this context. This thesis concludes by making a significant contribution to the field of academic mentoring by providing a deeper understanding of mentoring styles in graduate programs in Administration. The developed Academic Mentoring Styles Scale is a useful tool for training programs for mentors, enabling their continuous professional development and encouraging more adaptive mentoring practices. The Relational-Empathetic and Technical-Instrumental styles are not dichotomous but complementary, and mentors may adopt elements of both styles depending on the needs of their mentees, the type of research, and institutional demands.